2 - Quelles valeurs pour quel développement ? - Habib El Malki, (Africa Development, 1987)
The depth and duration of the present crisis calls for a new perspective on development. Thé challenge can no longer be limited to noting the "great strides" made by the productive forces - that is to growth per se - but that*Of formulating strategies which respond the questions such as: development for whom? and how? Although the ideology of growth is largely accepted this is not the case for its methodological, conceptual and theoretical implications. In other words, it is still difficult to reinstate the non-economic dimension because of ideologically based premises, received ideas... etc. Hqwever, a methodological shift which will give priority to non-economic dimensions and one which will take account of such qualitative dimensions such as history culture, values and peoples collective wisdom etc. can but promote the economic dimension. Such an approach has a double value: 1. It allows a better understanding of the specificity and limitations of the economic dimension of Third World societies. 2. It underscores the validity of an analysis based on national social projections than those which are based on development models.